Land management and conservation of the habitat of Bruguiera hainesii C.G. Rogers in Vietnam - Mai Phuong Pham; Thi Thu Trang Hoang; Xuan Dao Nguyen; Quoc Khanh Nguyen; Dinh Duy Vu (Journal of Degraded and Mining Lands Management)
Comprehending the bidirectional interactions between ecosystems and plant communities is essential for ensuring the conservation and sustainable development of Bruguiera hainesii. The study identified nine accompanying plant species within a range of 1.2-5.5 m, including five frequently encountered species and four commonly found ones. The research site is influenced by two distinct wind seasons: the Northeast monsoon (November to April) and the Southwest monsoon during the rainy season, with an average wind speed of 1.77 m/s. Correspondingly, the wave regime alternates with these seasons, featuring opposing directions. During the Northeast monsoon, wave heights average 2-2.5 m, while during the Southwest monsoon, they decrease to 1.5-1.7 m. The tidal regime in Con Dao is mixed semi-diurnal, with tidal ranges of 3-4 m at high tide and 1.5-2 m at low tide. Tidal currents primarily drive the flow regime, with dominant Northeast flow during early summer and seasonal shifts between winter and summer. Flow velocities range from 0.15 to 0.92 m/s, influenced by the Manning roughness coefficient. Sediment dynamics reveal that increased settling velocities correlate with higher suspended sediment concentrations, with total suspended sediment at point P1 approximately 70% greater than at point P2. These findings elucidate the seasonal and hourly dynamics of tidal waves and sediment transport, offering critical insights to support the effective conservation of B. hainesii.